Strategi Komunikasi Merek X dalam Proses Difusi Inovasi Alternative Channel di Kota Samarinda - Islam, Jeni Ananda Nur; Agustian, Jaka Farih; Sary, Kezia Arum; Rohmah, Ainun Nimatu (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
The purpose of this research is to explain the communication strategy applied by Brand X in the diffusion process of their alternative channel innovation. As one of the top brands of low/sugar-free sweetener brands, Brand X innovates alternative channels to answer the opportunities that present themselves. This research focuses on the stages of innovation-decision process, namely the knowledge stage, persuasion stage, decision stage, implementation stage and confirmation stage. The research method used is qualitative research method and data is collected through interviews and documentation studies. The results of this research show that at the knowledge stage, communicators conduct surveys and observations to each retail destination before introducing the innovation. This activity helps communicators in recognizing retail needs and becomes a reference in developing messages at the persuasion stage. At the decision stage, communicators utilize social media to establish communication with retailers who reject the innovation with the aim of building interpersonal relationships. At the implementation stage, communicators help retailers implement the innovation. However, it was found that in Samarinda, the communication at the confirmation stage was not consistent.